Rilascio dei biomarkers di danno miocardico dopo iniezione diretta per via percutanea di cellule staminali e terapia genica - Baldazzi, Federica <1976> (Alma Mater Studiorum - Università di Bologna, 2009)
Aims: We aimed to quantify the release of bio-markers of myocardial damage in relation to direct intramyocardial injections of genes and stem cells in patients with severe coronary artery disease. Methods and Results: We studied 71 patients with “no-option” coronary artery disease. Patients had, via the percutaneous transluminal route, a total of 11±1 (mean ± SD) intramyocardial injections of vascular endothelial growth factor genes (n=56) or mesenchymal stromal cells (n=15). Injections were guided to an ischemic area by electromechanical mapping, using the NOGA™/Myostar™ catheter system. ECG was monitored continuously until discharge. Plasma CKMB (upper normal laboratory limit=5 μg/l) was 2 μg/l (2-3) at baseline; increased to 6 (5-9) after 8 hours (p < 0.0001) and normalized to 4 (3-5) after 24 hours. A total of 8 patients (17%), receiving a volume of 0.3 ml per injection, had CKMB rises exceeding 3 times the upper limit, whereas no patient in the group receiving 0.2 ml had a more than two fold CKMB increase. No patient developed new ECG changes. There were no clinically important ventricular arrhythmias and no death. Conclusion: Direct Intramyocardial injections of stem cells or genes lead to measurable release of cardiac bio-markers, which was related to the injected volume.